2002
DOI: 10.1046/j.1365-2168.2002.02202.x
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality associated with pancreatogastrostomy and pancreatojejunostomy following partial pancreatoduodenectomy

Abstract: Pancreatogastrostomy is a safe and reliable method of reconstruction after PPD that may be associated with a lower leakage and mortality rate than pancreatojejunostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
84
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 24 publications
6
84
1
Order By: Relevance
“…The disruption of the anastomotic site is the cause of PF and is associated with stricture or occlusion of the anastomosis at early stages after PD. In contrast, the frequency of ARP is low with the ratio of 2% in pancreatogastrostomy [1], and 1.6% [1] to 2.2% [2] in pancreatojejunostomy. The strictured or occluded anastomosis at the late stage post-PD causes ARP [3].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The disruption of the anastomotic site is the cause of PF and is associated with stricture or occlusion of the anastomosis at early stages after PD. In contrast, the frequency of ARP is low with the ratio of 2% in pancreatogastrostomy [1], and 1.6% [1] to 2.2% [2] in pancreatojejunostomy. The strictured or occluded anastomosis at the late stage post-PD causes ARP [3].…”
Section: Introductionmentioning
confidence: 82%
“…The frequency of PF is low in patients with pancreatogastrostomy, with a rate of 0-12% [1], while it is more frequent among pancreatojejunostomy patients, with a rate of 10 to 20% [1]. Another study has reported that 14% of patients with pancreatoduodenectomy have suffered from PF [2].…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have been described, and these include duct-to-mucosa pancreaticojejunostomy (PJ), endto-end anastomosis with invagination of the pancreatic stump in a loop of jejunum, pancreaticogastrostomy (PG) with end-to-side and end-to-end anastomosis with invagination. Many studies showed a decreased leak rate with PG [22,23] than with PJ. In contrast, Yeo et al [5] showed that there is no difference in pancreatic leak rate following both PJ and PG.…”
Section: Discussionmentioning
confidence: 99%
“…PD nowadays represents a complex procedure and a challenge for the surgeon. Recently, the operative mortality rate after PD has significantly declined, while the incidence of postoperative morbidity remains high, from 40%-50% [1][2][3][4][5][6], and a recent series of 650 operations demonstrated a 30-day mortality of 1.4% [7]. The improved mortality is related to improve general management surgeon expertise and higher volume of procedures being performed in a hospital [5].…”
Section: Introductionmentioning
confidence: 99%